Duodenal perforation with Ascaris lumbricoides in a child: A case report - Agrawal, Archana; Aggarwal, Bindu; Maletha, Madhukar; Gupta, Sourabh (Indian Journal of Child Health, 2017)
Gastrointestinal infestation with Ascaris lumbricoides is common in temperate and tropical countries. Although heavy worm infestation produces wide range of acute abdominal complications, duodenal perforation in association with ascariasis, especially in children, is rarely reported. We report a case of 5-year-old girl with duodenal perforation secondary to ascariasis.